Profiling research on PFAS in wildlife: Protocol of a systematic evidence map and bibliometric analysis. Issue 4 (24th October 2021) - Vendl, Catharina; Taylor, Matthew D.; Bräunig, Jennifer; Gibson, Matthew J.; Hesselson, Daniel; Neely, G. Gregory; Lagisz, Malgorzata; Nakagawa, Shinichi
Abstract: Per‐ and polyfluoroalkyl substances (PFAS) are a large group of manufactured chemicals. Since the beginning of their commercial production in the 1950s, PFAS have not only found their way into numerous industrial and commercial applications, but also into the bloodstream of much of the human population, the natural environment and wildlife. Exposure to high levels of PFAS poses a health risk for humans and animals, and may exacerbate the effects of other anthropogenic impacts faced by wildlife species. To gain a comprehensive overview of the abundance and distribution of PFAS research on wildlife species, and to better understand the drivers of this research, we will collate the available literature into a systematic evidence map and perform bibliometric analyses. The systematic mapping will present the distribution of research evidence that exists on PFAS in wildlife. The bibliometric analysis will provide an insight into the historical trends, interdisciplinarity, connectedness and the impact of the individual papers. We will conduct a systematic literature search on Scopus, Web of Science and 10 other databases using predefined search strings. We will screen title, abstract and keywords first. We will then screen full‐text papers. Two reviewers will be involved in the screening process. We will only consider publications in English, peer‐reviewed articles, preprints and theses. We will include papers reporting concentrations of any of 34 main PFAS types (based on a previous study) in wild animals. We will assess all publications included in the systematic map for predetermined indicators of quality and potential study‐level biases. In addition, we will use bibliometric records from Scopus to perform impact and network analyses. We will present the results using a narrative summary, tables and colour‐coded maps, bar and network plots. Results and associated database will be available on a dedicated freely accessible website. This study will provide critical insight into the gaps and clusters of the literature with regard to the PFAS concentrations in wildlife. Our study will inform and direct future research efforts to fill the gaps revealed. Abstract : Per‐ and polyfluoroalkyl substances (PFAS) are a large group of manufactured chemicals that can be found everywhere and wildlife is no exception. Our protocol describes the systematic mapping and bibliometric analysis of available literature of PFAS in wildlife. The results of the study will inform future research in PFAS and conservation management.